The Groote Schuur Hospital nurses' experience - U. Brown; A. Kollmitz (AOSIS, 1984)
It can be said that, in nursing circles, 1984 has been the Year of Evaluation. This has certainly been the case in the Nursing Education Department of Groote Schuur Hospital.